Gibberellic acid concentrations in seed propagated artichoke - Miguel, Alfredo; Baixauli, Carlos; Aguilar, José M.; Giner, Alfonso; Maroto Borrego, José V.; Lopez, S.; San Bautista, Alberto; Pascual, B. (2017)
In Spain, the artichoke crop is interesting for autumn-winter production. With vegetative propagated cultivars, like ‘Blanca de Tudela’ or ‘Violeta de Provenza’, the harvest starts at the beginning of autumn and finishes at the end of spring. The currently available seed propagated cultivars are not as early as the asexually propagated ones mentioned above. For this reason, to obtain production in the autumn-winter cycle with seed propagated cultivars, it is necessary to use the earlier ones, to plant at the beginning of the summer and to spray plants with gibberellic acid (GA) to substitute the lack of vernalization requirements. The trials were conducted during three seasons. In 1999-2000, using the cultivar ‘A-106’ and ‘A-108’, two concentrations of GA (10 and 30 ppm) were compared with untreated plants. In the 2000-2001 season, using the cultivars ‘Lorca’ and ‘Nun 98465’ and in the 2001-2002 season, using the cultivars ‘A-106’ and ‘Nun 9409’, three concentrations of GA (10, 30 and 50 ppm) were also compared with untreated plants. The cultivars ‘A-106’ and ‘Lorca’ are similar to Imperial Star and earlier than the hybrids ‘Nun 98465’ and ‘Nun 9409’. In the earlier cultivars, GA applications increased early yields. No significant differences in yield or head weight were found among the GA concentrations tested. In the latest cultivars (‘Nun 98465’ and ‘Nun 9409’), higher concentrations of GA slightly increased early yields, but not high enough to be comparable to the earlier ones.